Socialization of Scientific Paper Writing Strategy for National Competition at State Senior High School 01 Namorambe, Deliserdang Regency : Sosialisasi Strategi Penulisan Karya Tulis Ilmiah Kompetisi Tingkat Nasional Di Sma Negeri 01 Namorambe Kab. Deliserdang - Sinambela, Yusnia; Sitorus, Nurianti Sitorus; Riana, Meisi Riana; Juwairiah, Juwairiah; Efrizal, Efrizal; Sinaga, Rommel Sinaga (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
The State Polytechnic of Creative Media PSDKU Medan carries out the Tri Dharma of Higher Education, one of which is to carry out community service. As a form of responsibility to the community, it is carried out through coaching and approaching the community. The young generation of Indonesia as the successors of the nation certainly needs a place to accommodate and test their scientific ideas in depth. As part of the mental revolution, P3M State Polytechnic of Creative Media PSDKU Medan is expected to take a special role in cultivating scientific thinking in Indonesian youth, especially high school students in North Sumatra. The existence of socialization and training in writing scientific papers is expected that students will be more enthusiastic in writing and participating in scientific paper competition programs organized by institutions or research institutions as well as educational institutions. With the active participation of students in scientific paper competitions, quality student works will emerge which are the seeds for solving problems in the surrounding environment, because from this initial work it will be developed into works that are more widely useful